Tatbiq Thariqah at-Tafkir wa al-Iqtiran wa al-Musyarakah fi Tarqiyah Nataij Maharah al-Kitabah li Thullab as-Shaf as-Tsamin fi Ma'had al-Islami Insan Mulia Punggur - Siti Hamidah; Nailul Izzah; Kholida Nur (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
This study aims to examine the impact of the Think Pair Share (TPS) method on improving the writing skills (maharoh kitabah) of eighth-grade students at Ponpes Insan Mulia Punggur. The research background highlights challenges faced by students, such as low interest and active participation in learning writing skills. Using a quantitative experimental approach, 28 students were divided into an experimental class (using TPS) and a control class (without TPS). Data collection involved pretests, posttests, observations, and interviews. Results showed a significant improvement in the experimental class compared to the control class. In the experimental group, the average pretest score was 65.3 (57% mastery), increasing to 79.29 (93% mastery) in the posttest. Meanwhile, the control group’s average pretest score was 52.5 (14% mastery), rising to 61.42 (36% mastery) in the posttest. This aligns with previous studies demonstrating TPS's effectiveness in enhancing student learning outcomes